Alantolactone induces apoptosis through ROS-mediated AKT pathway and inhibition of PINK1-mediated mitophagy in human HepG2 cells. Issue 1 (4th December 2019) - Kang, Xing; Wang, Hijuan; Li, Yanwei; Xiao, Ying; Zhao, Lili; Zhang, Tingting; Zhou, Shaohe; Zhou, Xiaolun; Li, Yi; Shou, Zhexing; Chen, Chao; Li, Bin
Abstract: Alantolactone (Ala), a major sesquiterpene lactone extracted from Inula helenium, exerts potent anti-tumour activities in various cancers. However, the underlying mechanism of such activities is still ambiguous. This study focused on evaluating the anti-tumour effects and molecular mechanisms of Ala on HepG2 cells. Our results demonstrated that Ala might inhibit cellular proliferation, induce G2/M phase arrest and apoptosis in HepG2 cells. Specifically, this study confirmed that Ala induced G2/M phase arrest by upregulating p21, downregulating cyclin A1 and cyclin B1, and promoting cellular apoptosis by increasing the expression of cleaved caspase-3 and PARP. Furthermore, Ala caused an increase in reactive oxygen species (ROS) level and inhibition of ROS production significantly prevented Ala-induced apoptosis. Interestingly, the accumulation of ROS, in turn, suppressed the downstream AKT signalling. Finally, mitophagy of Ala-treated HepG2 cells was observed by Mito/Lyso staining. Mitophagy was significantly inhibited by downregulation of the expression of PINK1 and Parkin proteins. The inhibition of mitophagy by a mitophagy inhibitor was found to markedly enhance Ala-mediated apoptosis and growth inhibition in HepG2 cells. Consequently, Ala induced cellular apoptosis via ROS-mediated suppression of AKT signalling and inhibition of PINK1-mediated mitophagy. Thus, Ala has potential to be used for the treatment of liver cancer.